Post-Electoral Violence and National Development in Nigeria - Badmus, Bidemi Gafar (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
Election is generally accepted in all climes of the world as the hallmark of democracy. Political scientists and development theorists link free, fair and credible elections to democratic governance, peace and development. In brief, they argue that free, fair and credible elections provide the basis for the emergence of democratic, accountable and legitimate governments with the capacity to initiate and implement clearly articulated development programmes. Again, they claim that free, fair and credible elections empower the electorate to hold the government accountable and to demand strong credentials and feasible development agenda from prospective government officials. In other words, free, fair and credible elections bestow on governments the legitimate authority to, on one hand, initiate and implement policies; while on the other hand, they empower the citizens to hold governments accountable for their actions and/or inactions. Credible elections are, therefore, sine qua non for democratic governance, political stability and national development